Chemical Composition and Antioxidant, Analgesic, and Anti-Inflammatory Effects of Methanolic Extract of Euphorbia retusa in Mice - Allagui, Mohamed Salah; Hfaiedh, Najla; Bouguerra, Wided; Ncib, Sana; Feriani, Anouar; Rjeibi, Ilhem; Sdayria, Jazia; Elfeki, Abdelfattah (Pain research & management, 2018)
Plants provide an alternative source to manage different human disorders due to various metabolites. The aim of this study is to investigate the phytochemical constituents of the methanolic extracts of Euphorbia retusa and to evaluate their antioxidant, anti-inflammatory, and analgesic activities. The phytochemical results obtained by HPLC and by chemical assay reactions have revealed the richness of the methanolic extract of E. retusa in active compounds, in particular polyphenols, flavonoids, and tannins. The methanolic extract shows significant antioxidant activities in vitro, in the DPPH and the FRAP assays. The antinociceptive activity was evaluated using acetic acid and hot-plate models of pain in mice. The anti-inflammatory activity was evaluated by carrageenan-induced paw edema. Oral pretreatment with the methanolic extract of E. retusa (200 mg/kg) exhibited a significant inhibition of pain induced either by acetic acid or by the heating plate and in a manner comparable to the standard drug paracetamol. E. retusa significantly reduced paw edema starting from the 3rd hour after carrageenan administration by increasing the activity of antioxidant enzymes (SOD, CAT, and GPx) in liver and paw tissues and decreasing the levels of MDA. These results may confirm the interesting potential of this plant as a treatment of various inflammatory and pain diseases.